2021
DOI: 10.3390/clockssleep3040039
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction and Daylight Saving Time Transitions: Is There a Risk?

Abstract: Available evidence on the risk of acute myocardial infarction (AMI) in the days after the spring daylight saving time (DST) transition suggests either a modest increase or no risk increase. Partial sleep deprivation and enhanced circadian clock misalignment have been implicated as the underlying mechanisms for increased AMI risk, probably via enhanced thrombo-inflammatory processes and activation of the sympathetic nervous system. Most of the studies, as we suggest as a perspective here, have used potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Some studies highlight an increase in hospital admissions for AMI in the spring transition. 4,8,36,37 However, to our knowledge, only 2 studies showed an increased risk of AMI admissions associated with the autumn DST transition. Making it clear that any disruption of the circadian rhythm increases the risk of an acute CV event or MACE.…”
Section: Discussionmentioning
confidence: 81%
“…Some studies highlight an increase in hospital admissions for AMI in the spring transition. 4,8,36,37 However, to our knowledge, only 2 studies showed an increased risk of AMI admissions associated with the autumn DST transition. Making it clear that any disruption of the circadian rhythm increases the risk of an acute CV event or MACE.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, we found that the shift to DST aggravates later chronotypes' dependence on high-quality sleep to prevent procrastination the next day (Culić and Kantermann, 2021 ). Our findings thus reveal the consequences of the shift to DST, especially for later chronotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In chronobiological terms, this may be framed as re-entrainment in the immediate weeks following the clock change versus ongoing increased circadian desynchrony/social jetlag under DST. This distinction may be important in understanding the adverse health and behavioral consequences associated with the spring transition to DST, and may be a contributor to the recent suggestion that the cardiovascular risk associated with the spring change to DST is understated due to the selection of inappropriate reference periods during which circadian desynchrony will still be high ( Čulić and Kantermann, 2021 ).…”
Section: Being In Dst Versus Switching To Dstmentioning
confidence: 99%
“…This is a highly pertinent issue given proposals in various jurisdictions where the options presented to the public are narrowed to yes/no questions on abolishing the clock changes and adopting permanent DST, potentially resulting in less chronobiologically favorable scenarios due to detrimental effects of increased year-round social jetlag (e.g., poorer sleep health, impaired mood and cognition, poorer cardiometabolic health) outweighing the benefits of eliminating the transitions (decreased risk of cardiovascular events and road traffic accidents in the week(s) following clock change). Such a risk/benefit calculation is complicated by uncertainties around the magnitude of effects of social jetlag in relation to health outcomes, and the ongoing discussion on risks associated with the transitions ( Čulić and Kantermann, 2021 ).…”
Section: Being In Dst Versus Switching To Dstmentioning
confidence: 99%
See 1 more Smart Citation